Adipose afferent reflex response to insulin is mediated by melanocortin 4 type receptors in the paraventricular nucleus in insulin resistance rats. (20th April 2015) - Ding, L.; Tong, N.; Feng, X.‐M.; Chen, D.; Wang, H.‐S.; Wang, Y.; Li, Y.; Zhu, G.‐Q.; Zhou, Y.‐B.
Abstract Background Adipose afferent reflex (AAR) contributes to sympathetic activation and hypertension. Paraventricular nucleus (PVN) plays an important role in AAR and sympathetic outflow. The aim of the present study was to determine whether PVN mediates AAR response to insulin in a rat model of insulin resistance (IR). Methods Male Sprague‐Dawley rats were randomly divided into Control and IR groups. Insulin resistance was induced by supplementing fructose (125 g L−1, 12 weeks) in the drinking water. Renal sympathetic nerve activity (RSNA) and mean arterial pressure (MAP) were recorded in anesthetized rats. AAR was evaluated by the RSNA and MAP responses to injection of capsaicin into four sites of right inguinal white adipose tissue. Results Rats in IR group showed a rise in plasma noradrenaline (NE), glucose, insulin and triglyceride levels, left ventricular weight, systolic blood pressure, homeostasis model assessment of insulin resistance (HOMA‐IR) and PVN glucose and insulin levels, melanocortin 4 type receptors (MC4Rs) protein expression, but not MC3Rs and insulin receptors. Compared with Control group, AAR in IR group was significantly enhanced, which contributed to the elevation of NE level; and insulin microinjection into the PVN or the third ventricle significantly strengthened AAR, which was attenuated by pre‐treatment with MC4Rs antagonist HS024 and anti‐insulin affibody, respectively, but not insulin receptors antagonist S961. Conclusion The enhanced AAR participates in sympathetic activation in IR, which can be strengthened by PVN insulin. PVN MC4Rs mediate the AAR response to insulin in IR, but not MC3Rs and insulin receptors.